Efficacy of modified thoraco-laparoscopic Ivor-Lewis versus traditional thoraco-laparoscopic Ivor-Lewis for esophageal cancer: Propensity score-matched analysis - Hong, Ziqiang; Gou, Wenxi; Lu, Yingjie; Wu, Xusheng; Sheng, Yannan; Cui, Baiqiang; Bai, Xiangdou; Jin, Dacheng; Gou, Yunjiu (Frontiers in Oncology, 2023)
Objective: To compare the clinical results of the modified Ivor-Lewis procedure, which preserves the odd vein, thoracic duct and surrounding tissues, with the conventional Ivor-Lewis procedure, which removes these tissues, for the treatment of esophageal squamous cell carcinoma, and to evaluate whether surgery for esophageal cancer requires the removal of the odd vein, thoracic duct and surrounding tissues. Methods: To retrospectively analyze the clinical data of patients with esophageal cancer treated by thoracic-laparoscopic Ivor-Lewis procedure admitted to the Department of Thoracic Surgery of Gansu Provincial People's Hospital from September 2017 to September 2019. According to the surgical method, they were divided into modified thoracolaparoscopic Ivor-Lewis (modified group) and conventional thoracolaparoscopic Ivor-Lewis (conventional group). Propensity score matching analysis (PSM) was used to reduce the selection bias of confounding factors. Results: A total of 245 patients with esophageal cancer who underwent thoracic-laparoscopic Ivor-Lewis were enrolled in the study. There were 124 cases in the modified group and 121 cases in the traditional group. The differences in age and T-stage between patients in the conventional and modified groups were statistically significant. After PSM, the above factors were no longer statistically significant. 86 patients in each group after PSM. The modified group had shorter operative time, less intraoperative bleeding, and less chest drainage 3 days after surgery than the conventional group, with statistically significant differences (p<0.05). There was no significant difference in local recurrence and distant metastasis after surgery between the two groups, and the difference was not statistically significant (p>0.05). There was also no statistically significant difference in the 3-year postoperative survival rate between the modified and conventional groups (44.2% vs. 41.9%) (p>0.05). Conclusion: The modified Ivor-Lewis procedure, which preserves the odd vein, thoracic duct, and surrounding tissue, reduces surgical trauma in esophageal cancer, does not increase postoperative recurrent metastases, and can achieve the same long-term outcomes as expanded surgery.